Leprosy in families: Clinicoepidemiological profile from a tertiary care centre - Sukumaran Pradeep Nair (Wolters Kluwer Medknow Publications, 2017)
Objectives: The primary objective of this retrospective study was to determine the prevalence of leprosy in families, and the secondary objective was to study the clinicoepidemiological features of leprosy in families. Results: There were a total of 901 cases of leprosy who attended our leprosy centre during this 18 year period. There were 49 cases of leprosy in this group whose family members also had documented leprosy (n = 49). A total of 61 family members of the index cases were affected by leprosy, thus making a total of 110 cases. There were 30 males (61.22%) and 19 females (38.78%) in the index cases. The age group of 21-40 years comprised the maximum number of cases in the index group, accounting for 24.49%. Borderline tuberculoid (BT) was the commonest type of leprosy in both the index cases and family members accounting for 48.98% and 55.74%, respectively. Conjugal leprosy was present in 16 couples. In 68.75% of leprosy in couples, one member was of the lepromatous type. Children (10-15 years age group) accounted for 10 cases in this study (9.09%). In children, 90% of the cases had one member with lepromatous leprosy. Conclusions: The prevalence of leprosy in families in this study was 5.44%. BT was the most common type of leprosy in both the index cases and family members. The prevalence of conjugal leprosy was 1.78%, with majority of the partners having the lepromatous type. Of the affected children, 90% had family members with lepromatous type of leprosy.